Biological variation in two Anopheles vestitipennis populations with different feeding preferences in Southern Mexico. - Ulloa García, Armando; Rodríguez, Mario Henry; Arredondo Jiménez, Juan Ignacio; Fernández Salas, Ildefonso (2005)
The lengths of gonotrophic cycle and egg development and survival rate were studied in Anopheles vestitipennis collected in horse and human-baited traps in southern Mexico. The gonotrophic cycle duration was estimated using cross-correlation analysis, whereas the survival rate was assessed using a vertical method. Daily changes of parity rates gave significant correlation indices at 3 and 4 days in the zoophilic and anthro-pophilic populations, respectively. The minimum time required to develop mature eggs after blood feeding was 54 and 60 h, and the survival rate was 0.93 and 0.88 in zoophilic and anthropophilic female mosquito populations, respectively. These biological differences provide additional support for the existence of subpopulations with distinctive feeding preferences within An. vestitipennis in southern Mexico.